Inkjet‐Printed Phase Change Memory Devices - Hanglin He; Dhananjeya Kumaar; Kevin Portner; Till Zellweger; Florian M. Schenk; Simon Wintersteller; Vitor Vlnieska; Alexandros Emboras; Vanessa Wood; Maksym Yarema (Advanced Electronic Materials, 2024)
Abstract Phase change memory (PCM) is among the most promising candidates for the next generation of storage‐class and main memory systems in the computing era beyond Moore's law. However, the widespread installment of PCM devices is limited by the high price‐per‐bit and complex fabrication process. In this paper, it is shown that functional PCM memory devices can be printed, proving low‐cost avenues for non‐silicon memory technologies. Taking Ge‐Sb‐Te (GST) as a case study, PCM inks are prepared and optimize their structural, rheological, and printing parameters. GST layers are then printed onto PCM devices in the planar configuration, showing excellent performance, such as non‐volatility, resistivity contrast, low cycle‐to‐cycle variability, and endurance of at least 100 cycles. This paper provides a novel approach to liquid‐based engineered PCM devices through inkjet printing, enabling patterned memory layers, lower price‐per‐bit, and customizable multi‐material PCM arrays.